Biosphere cycles. Senior energy flow and nutrient cycles. (Warriewood, N.S.W. Classroom Video, 2003)
This video examines the workings of the Earth's biosphere. It discusses how the one way flow of energy from the sun underpins the continual recycling of molecules between living and non-living states. Featured in the video are: key nutrient cycles including carbon/oxygen, nitrogen and phosphorus; the research of Jean-Baptiste van Helmont; discussion on how human practices are impacting on nutrient cycles; an examination of how living things decompose, time-lapse sequences of decomposing organic matters; a case study of the workings of a major coffee farm.
Produced by Peter Beeh ; teachers notes, John Willis.
Keywords: Biosphere; Nutrient cycles; Earth (Planet)